Educação escolar indígena, intercultura e formação de professores (as) - uma pesquisa a partir das proposições da biologia do amor e da biologia do conhecimento de Humberto Maturana - Maders, Sandra (2013)
This research paper I present as Dissertation in Education, Training Line Knowledge and Professional Development (PPGE-UFSM), aim to contribute to theoretical and epistemological for Teacher Education (as) in general, and Education Indigenous School in particular, from the propositions of Biology and Biology Meet Amar, ie partirdo biological basis for human-relational perspective of intercultural dialogue. To develop this project Dissertation research activities were conducted a qualitative and theoretical-epistemological character. The framework that guided the "investigative and reflective gaze of the researcher" (BARCELOS, 2005) towards the "production of information search" (JACQUES GAUTHIER, 1998), is the establishment of dialogues that emphasize intercultural aspects (Canclini, 2003a ) with imaginary and representations on the issues of indigenous culture and teacher education in general and in particular for indigenous education. I believe that this work can become a work of great importance, because it will be the presentation of the search for alternatives to deal with the challenges posed to education, taking into account the sweeping changes occurring in the world today. Thus, a major goal of this research is to explain the contributions of some epistemological propositions of Humberto Maturana to building an education with indigenous communities to promote an education guided respect and cultural dialogue. During the research, it may be observed that for this to happen there Indigenous Education who pay attention to emotions such as caring, listening and acceptance of differences, both in school, and in society in general, always seeking perspective intercultural dialogue.